2018
DOI: 10.1016/j.marpolbul.2018.05.060
|View full text |Cite
|
Sign up to set email alerts
|

Microplastic pollution on Caribbean beaches in the Lesser Antilles

Abstract: Here we investigate microplastics contamination on beaches of four islands of the Lesser Antilles (Anguilla, St. Barthélemy, St. Eustatius and St. Martin/Maarten). These islands are close to the North Atlantic subtropical gyre, which contains high levels of microplastics. On average 261 ± 6 microplastics/kg of dry sand were found, with a maximum of 620 ± 96 microplastics on Grandes Cayes, Saint Martin. The vast majority of these microplastics (>95%) were fibers. Levels of microplastics differed among islands, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(23 citation statements)
references
References 51 publications
3
16
0
Order By: Relevance
“…In most studies, no differentiation is made between particle and fiber concentrations ( Table 1). The high fiber proportion in the present study corroborated the global trend to a predominance of fibers as observed on beaches in Belgium (Claessens et al 2011;Van Cauwenberghe et al 2013a), France (Bosker et al 2018), Germany Published in Environ. Sci.…”
Section: Possible Origins Of Particles and Fibers On The Côte D'opalesupporting
confidence: 89%
“…In most studies, no differentiation is made between particle and fiber concentrations ( Table 1). The high fiber proportion in the present study corroborated the global trend to a predominance of fibers as observed on beaches in Belgium (Claessens et al 2011;Van Cauwenberghe et al 2013a), France (Bosker et al 2018), Germany Published in Environ. Sci.…”
Section: Possible Origins Of Particles and Fibers On The Côte D'opalesupporting
confidence: 89%
“…Intricate studies have looked at the impact of microplastics on different organisms, both in their natural habitat and in laboratory settings. There is some trepidation about the impact of microplastics on biodiversity, which has been expressed in recent papers [63] [64] [65]. Thus, it has been shown that larger invertebrate species ingest microplastics, mistaking them for their natural prey because of similarities in shape, size and color, e.g., mistaking them for plankton [66]- [73].…”
Section: Composition Of Microplastics Their Distribution In the Envimentioning
confidence: 99%
“…[45]. The study conducted on Caribbean beaches at Lesser Antilles by Bosker et al (2018) showed a concentration at the range of 261 kg dry weigh (d.w) [46]. Similar to these studies, approximately, 5.25 trillion particles weighing 268940 tons float in the world's oceans surface [47].…”
Section: Beaches Coastlines and Shorelinesmentioning
confidence: 82%
“…Piperagkas et al (2019) have explained this distribution by the environment factors as well as the winds, influencing their own properties (shapes, size, colors, etc.) [45]. The study conducted on Caribbean beaches at Lesser Antilles by Bosker et al (2018) showed a concentration at the range of 261 kg dry weigh (d.w) [46].…”
Section: Beaches Coastlines and Shorelinesmentioning
confidence: 99%